Environmental Quality of Prambanan Temple and Ratu Boko Temple’s Green Open Space based on Soundscape and Guild of Bird - Utami, Inggita; Yahya, Eva Nurulia; Afriandini, Wida; Dwipayana, Ajeng Silvi; Utami, Salsa Aprilia; Meilina Arliani, Baiq Dara; Ramadhani, Khairunnisrina (Journal of Biotechnology and Natural Science, 2022)
Sleman Regency has the most temple cultural heritage in Yogyakarta, supported by Green Open Space (GOS). The area is a habitat for urban birds and can be used as an indicator of environmental quality. This study aims to analyze the environmental quality based on the soundscape and character of the bird community in the GOS of Prambanan Temple and Ratu Boko Temple. Sound recordings were taken with a smartphone, and the recording time was set using the Arbimon touch in the morning, afternoon, and evening. The sound recordings are used to calculate acoustic indexes. The sound recordings and spectrograms are processed to identify bird species and calculate the Bird Community Index. The number of bird species was higher in the Ratu Boko area. According to the NDSI value, the sound of biophony at Ratu Boko Temple is more dominant than anthrophony and geophony. The environmental quality in the Prambanan Temple area is in the low category than in the Ratu Boko Temple area, which is classified as a medium category. The area's topography, the arrangement of vegetation, and the noise of vehicles due to the proximity to the highway affect the environment quality in temple areas.